Overt and Covert Buddhism: The Two Faces of University-Based Buddhism in Beijing - Chadwin, Joseph (Religions, 2020)
As more and more students in China turn to religion, it follows that an increasing number of students in Chinese universities self-identify as Buddhist. Chinese academia has a tendency to treat this as problematic, offering reasons for this trend as well as solutions but neglecting to examine the nature of student belief and identity. By utilising two case studies, this paper seeks to demonstrate how the Buddhist identity and practice of self-proclaimed Buddhist students in Beijing can manifest in two very different ways: overtly or covertly. More specifically, each case study provides an example of students in Beijing who very much break with the commonly held perception that students in China who self-identify as religious have a fundamentally flawed and limited understanding of their religion and rarely actually practice it.